SERVICES CANCER DETECTION SYSTEM USING K-NEAREST NEIGHBOURS(K-NN) METHOD AND NAÏVE BAYES CLASSIFIER - Sri Rezeki Candra Nursari; Nanda Mahya Barokatun Nisa (STMIK Pringsewu Lampung, 2020)
According to WHO (World Health Organization) data, every 2 minutes a woman dies. In Indonesia alone, 40 - 45 women are diagnosed with cervical cancer every day. Of those diagnosed, around 20-25 die from cervical cancer. About 95% more cervical cancer is caused by infection with the HPV virus or the human papilloma virus and an estimated death rate reaches 270,000 deaths each year. Cervical cancer occupies the third rank type of cancer in the world after breast and lung cancer, because the symptoms are not very visible at an early stage, so it is referred to as